Understanding cultural policy : government and the arts and culture in the United States - Rosenstein, Carole (Routledge, 2024)
"This textbook provides an introduction to cultural policy in the US, enabling both students and practitioners to understand how government impacts the arts and culture. Starting with an historical overview of why and how the US developed a national cultural policy, the book goes on to trace the contemporary system of national, state, and local arts and cultural agencies through which that policy is put into practice. Readers are provided both in-depth frameworks for conceptualizing how government regulation and provision shape the arts and culture and carefully illustrated examples of cultural policy in action. Covering critical issues in US cultural policy such as the Culture Wars, culture-led development and gentrification, and field-wide data and research capacities, the book builds a bridge between theory, practice, and politics in the arts and culture. This new edition includes enhanced visualizations and policy maps, expanded policy labs, and a new section on cultural policy during COVID-19. The result is a text that is essential reading for students and reflective practitioners of arts and cultural management and administration"-- Provided by publisher.
Keywords: Cultural property -- Protection -- United States -- Textbooks.; Art and state -- United States -- Textbooks.; United States -- Cultural policy -- Textbooks.; elektronické knihy; electronic books